Analysis of Hypertension Risk Factors in Ship's Men: The Role of Age, Smoking Habit, and Noise Exposure - Ismi Elya Wirdati; Fadhila Rahman Nugoroho (International Journal Of Health Science, 2025)
Hypertension is a critical health indicator that reflects an individual's cardiovascular condition. This study aims to analyze risk factors associated with hypertension among seafarers in Semarang, focusing on age, smoking habits, and noise exposure. Using a cross-sectional design, the study involved 43 seafarers from three ships at Tanjung Mas Port. Data were collected through questionnaires and blood pressure measurements using a sphygmomanometer, while noise exposure was measured with a sound level meter. The results showed a significant association between age and blood pressure, with individuals over 30 years of age having higher levels of prehypertension and hypertension (p = 0.021). Conversely, no significant correlation was found between smoking habits (p = 0.880) or noise exposure (p = 0.290) and blood pressure levels. These results suggest that while age is a significant risk factor for hypertension, smoking and noise exposure may not have a direct impact. This study highlights the need for comprehensive health monitoring and interventions targeting lifestyle changes among seafarers to reduce the risk of hypertension and improve overall health and safety in the maritime work environment.